2018
DOI: 10.1007/978-3-030-01461-2_8
|View full text |Cite
|
Sign up to set email alerts
|

$$Q|SI\rangle $$Q|SI⟩ : A Quantum Programming Environment

Abstract: This paper describes a quantum programming environment, named Q SI⟩ a . It is a platform embedded in the .Net language that supports quantum programming using a quantum extension of the while-language. The framework of the platform includes a compiler of the quantum while-language and a suite of tools for simulating quantum computation, optimizing quantum circuits, and analyzing and verifying quantum programs. Throughout the paper, using Q SI⟩ to simulate quantum behaviors on classical platforms with a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…The acidity of the supported POM does not correlate with the trend of hydrocracking activity of the examined catalysts. For example, it was reported that POM supported over SiO 2 has higher acidity strength than POM supported over alumina, but the hydrocracking activity of Ni‐POM/Al 2 O 3 is higher than the hydrocracking activity of Ni‐POM/SiO 2 . However, the results are correlated with the pore radius size of supports.…”
Section: Resultsmentioning
confidence: 99%
“…The acidity of the supported POM does not correlate with the trend of hydrocracking activity of the examined catalysts. For example, it was reported that POM supported over SiO 2 has higher acidity strength than POM supported over alumina, but the hydrocracking activity of Ni‐POM/Al 2 O 3 is higher than the hydrocracking activity of Ni‐POM/SiO 2 . However, the results are correlated with the pore radius size of supports.…”
Section: Resultsmentioning
confidence: 99%
“…Assembly languages are introduced as human-readable representation of the interface to hardware (or machine code). But existing quantum assembly languages either incorporate too high-level constructs to be directly implemented by a microarchitecture (including QASM-HL [11], il [12], f-QASM [13], etc. ), or are too restricted to provide a comprehensive abstraction of the quantum hardware which can support the required ow control (including OpenQASM [14], MIS [1], etc.).…”
Section: Introductionmentioning
confidence: 99%
“…In part due to the increasing viability of quantum computing and the scaling of NISQ [28] devices, there has been a recent explosion in quantum programming tools. Such tools range from software development kits (e.g., Qiskit [5], ProjectQ [32], Strawberry Fields [19], Pyquil [30]) to Embedded domain-specific languages (e.g., Quipper [11], Qwire [27], Q|SI [22]) and standalone languages and compilers (e.g., QCL [26], QML [2], ScaffCC [16], Q# [33]). Going beyond strict programming tools, software for the synthesis, optimization, and simulation of quantum circuits and programs (e.g., Revkit [31], TOpt [15], Feynman [3], PyZX [20], Quan-tum++ [9], QX [17]) are becoming more and more abundant.…”
Section: Introductionmentioning
confidence: 99%